Legal and regulatory aspects of telecommunication submarine cables - Monaca, Aldo; Grazia Indelicato, Gioia Alessia Chiara (The International Hydrographic Review, 2025)
By Andrés Fígoli Pacheco, independently published (30 July 2024), 158 p., ISBN-13 979-8332883187